Antimicrobial, Antibiofilm, and Antioxidant Activity of Bacterial Cellulose and Bacterial Nanocellulose from Vinegar’s Mother Pellicles - AL-Ramlawee, Khadija H.; Al-Khalifawi, Essam Jassim (Iraqi Journal of Science, 2025)
Recent research indicates that bacterial cellulose (BC) and bacterial nanocellulose (BNC) exhibit promising adsorptive properties for antimicrobial agents, owing to their complex network structure, high surface area, and substantial porosity. The aim of this study was to analyze the impact of the antimicrobial, antibiofilm, activity of BC and BNC on different bacterial isolates, were collected from wounds and burn wound patients. Also, a study examined the antioxidant activity. In this study, (BC) and (BNC) was produced from vingar mothers. The Pathogenic bacterial isolates were collected from wounds and burn wound patients of different age groups. The antibiotic susceptibility testing by disk diffusion method and Vitek 2 compact system method. The antimicrobial activity of BC and BNC on different bacterial isolates by the Resazurin-based 96-well plate microdilution method. Detection of biofilm formation and Inhibition of Biofilm Formation was quantified using the 96-well tissue culture plate method (TCP). Finally, the DPPH radical scavenging assay was used to investigate the ability of (BC) and (BNC) to scavenge free radicals. Seventy bacterial isolates were collected from wounds and burn wound patients of different age groups. It belongs to five species: Citrobacter freundii, ten isolates; Escherichia coli, 17 isolates; Klebsiella pneumonia, 16 isolates; Pseudomonas aeruginosa, 15 isolates and Staphylococcus aureus, 20 isolates. The Antibiotic susceptibility testing by disk diffusion method and Vitek 2 compact system method showed that most bacterial isolates were resistant to the antibiotics used. The antimicrobial activity of BC and BNC on different bacterial isolates by the Resazurin-based 96-well plate microdilution method showed different results in tests bacteria using the minimum inhibitory concentration (MIC). The study found that 60 out of the 70 bacterial isolates were able to produce biofilm, accounting for 85.71% of isolates, while 10 isolates (14.28%) did not produce biofilm. The effect of the BC and BNC on the biofilm formation using SUB-MIC 1 shows that BC and BNC prevent the biofilm formation in 17 (78%) and 25 (100%) isolates. Meanwhile, SUB-MIC 2 of BC and BNC prevent biofilm formation in 10 (42%) and 23 (80%) isolates. The results show that the % PDDH Radical Scavenging Activity for BC was (10.316 and 75.122) when the concentrations were (1.95 and 1000) µg/ml, respectively. The % PDDH Radical Scavenging Activity for BNC was (14.806 and 98.837) when the concentrations were (1.95 and 1000) µg/ml respectively. The % PDDH Radical Scavenging Activity for AA was (16.213 and 98.940) when the concentrations were (1.95 and 1000) µg/ml respectively. The bacterial cellulose and bacterial nanocellulose are characterized by their antimicrobial, antibiofilm, and antioxidant properties, which allow for a wide range of medical, industrial, and environmental applications.